Chloramphenicol and phenobarbitone--a drug interaction. Issue 1 (January 1979) - Bloxham, R A; Durbin, G M; Johnson, T; Winterborn, M H
Abstract : Two infants with meningitis who were treated with phenobarbitone and high-dose chloramphenicol showed progressive falls in the peak blood levels of chloramphenicol. A standard chloramphenicol dose of 50 mg/kg daily would have produced subtherapeutic blood levels after only a few days. The importance of measuring serial blood chloramphenicol concentrations is stressed.